Isolation and characterisation of the fungus Spiromastix asexualis sp. nov. from discospondylitis in a German Shepherd dog, and review of Spiromastix with the proposal of the new order Spiromastixales (Ascomycota). Issue 7 (12th March 2014) - Rizzo, L.; Sutton, D. A.; Wiederhold, N. P.; Thompson, E. H.; Friedman, R.; Wickes, B. L.; Cano‐Lira, J. F.; Stchigel, A. M.; Guarro, J.
Summary The genus Spiromastix consists of several fungal species that have been isolated from soil and animal dung in various parts of the world. However, these species are considered to be of low pathogenic potential, as no cases of infections caused by these fungi have been reported. Here, we describe the clinical course of discospondylitis in a dog from which a fungus was cultured from a biopsy and identified as a Spiromastix species by morphologic characteristics and sequencing. Phylogenetic analysis determined this to be a new species, Spiromastix asexualis, which is described, and a new order, Spiromastixales, is proposed.